Predation and Crypsis in the Evolution of Electric Signaling in Weakly Electric Fishes - Stoddard, Philip K.; Tran, Alex; Krahe, Rüdiger (Frontiers in Ecology and Evolution, 2019)
Eavesdropping by electroreceptive predators poses a conflict for weakly electric fish, which depend on their Electric Organ Discharge (EOD) signals both for navigation and communication in the dark. The EODs that allow weakly electric fish to electrolocate and communicate in the dark may attract electroreceptive predators such as catfishes and Electric Eels. These predators share with their prey the synapomorphy of passive electric sense supported by ampullary electroreceptors that are highly sensitive to low-frequency electric fields. Any low-frequency spectral components of the EOD make weakly electric fish conspicuous and vulnerable to attack from electroreceptive predators. Accordingly, most weakly electric fish shift spectral energy upwards or cloak low-frequency energy with compensatory masking signals. Subadults and females in particular emit virtually no low-frequency energy in their EODs, whereas courting males include a significant low-frequency component, which likely attracts females, but makes the signals conspicuous to predators. Males of species that coexist with the most predators tend to produce the least low-frequency signal energy, expressing sexual dimorphism in their signals in less risky ways. In these respects, electric signals follow the classic responses to opposing forces of natural and sexual selection, as exemplified in the visual signals of guppies and the acoustic signals of Túngara frogs. Unique to electric fish is that the electric signal modifications that help elude detection by electroreceptive predators are additions to the basal signal rather than losses of attractive components. These enhancements that enable crypsis are energetically costly, but have also provided the evolutionary substrates for subsequent sexual selection and species identity characters.